1981
DOI: 10.3171/jns.1981.54.3.0289
|View full text |Cite
|
Sign up to set email alerts
|

Further experience in the management of severe head injury

Abstract: A prospective and consecutive series of 225 patients with severe head injuries who were managed in a uniform way was analyzed to relate outcome to several clinical variables. Good recovery or moderate disability were achieved by 56% of the patients, 10% remained severely disabled or vegetative, and 34% died. Factors important in predicting a poor outcome included the presence of intracranial hematoma, increasing age, abnormal motor responses, impaired or absent eye movements or pupil light reflexes, early hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
164
0
17

Year Published

1984
1984
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 602 publications
(190 citation statements)
references
References 23 publications
9
164
0
17
Order By: Relevance
“…There was no correlation between the presence of systemic lesions associated with TBI and lethality resulting from TBI in this casuistic (p = 0.373), as also demonstrated by other studies 14,15,16 .…”
Section: Discussionsupporting
confidence: 65%
“…There was no correlation between the presence of systemic lesions associated with TBI and lethality resulting from TBI in this casuistic (p = 0.373), as also demonstrated by other studies 14,15,16 .…”
Section: Discussionsupporting
confidence: 65%
“…[3,17,18,20] Information from the Traumatic Coma Data Bank indicates that lowered CPP resulting from hypotension or increased ICP is associated with a poor outcome following head injury. [3,17] Pietropaoli, et al, [27] also found that intraoperative hypotension occurring in severely head injured patients undergoing surgical procedures within 72 hours of admission to the hospital was associated with a significant increase in mortality rates and also a significant decrease in GOS scores compared to those seen in head-injured patients who did not become hypotensive during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results of these studies indicate that such patients may benefit from treatment with DS hypertonic solution, patients with head injury have not been included into these studies. [38] It has been shown that DS hypertonic solution reduces intracerebral pressure (ICP) in animals with head injury. Berger et al [39] have compared the ability of hypertonic DS with that of hypertonic mannitol to reduce intracranial hypertension that develop due to focal cerebral lesions and intracranial mass and have reported that hypertonic DS provides higher brain perfusion pressure than mannitol.…”
Section: Discussionmentioning
confidence: 99%